Relationship between liver fibrosis and in-hospital outcomes in patients with acute coronary syndrome undergoing PCI. (3rd October 2022) - Biccire, F G; Barilla, F; Sammartini, E; Dacierno, E M; Tanzilli, G; Pastori, D
Abstract: Background: Patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) still experience a high rate of in-hospital complications. Liver fibrosis (LF) is a risk factor for mortality in the general population. However its prognostic role in ACS patients has been poorly investigated. Purpose: We investigated whether the presence of LF detected by the validated fibrosis-4 (FIB-4) score may indicate ACS patients at higher risk of poor outcome. Methods: In the prospective ongoing REAl-world observationaL rEgistry of Acute Coronary Syndrome (REALE-ACS), LF was defined by a FIB-4 score >3.25. The primary endpoint was in-hospital adverse events (AEs) including a composite of in-hospital cardiogenic shock, PEA/asystole, acute pulmonary edema and death. Results: A total of 469 consecutive ACS consecutive patients were enrolled. Overall, 21.1% of patients had a FIB-4 score >3.25. Patients with LF were older, less frequently on P2Y12 inhibitors (p=0.021) and admitted with higher serum levels of white blood cells (p<0.001), neutrophils to lymphocytes ratio (p<0.001), C-reactive protein (p=0.013), high-sensitive troponin T (p<0.001), creatin-kinase MB (p<0.001), D-Dimer levels (p<0.001). STEMI presentation and higher Killip class/GRACE score were more common in the LF group (p<0.001). 71 patients experienced 110 AEs. At the multivariate analysis including clinical and laboratory risk factors, FIB-4 >3.25 (OR 3.1, 95% CI 1.4 to 6.9), admission left ventricular ejection fraction% below median (OR 9.2, 95% CI 3.9 to 21.7) and Killip class ≥II (OR 6.3, 95% CI 2.2 to 18.4) were the strongest independent predictors of in-hospital AEs. Conclusions: LF detected by FIB-4 score >3.25 was associated with more severe ACS presentation and worse in-hospital AEs irrespective of clinical and laboratory variables. Funding Acknowledgement: Type of funding sources: None.